Public domain as an antidote conception to efforts to protect traditional cultural expressions (TCEs) - Thamrin Arthata Hutajulu (Westscience Press, 2024)
This paper analyzes how the public domain conception applied in the provisions of Intellectual Property Rights is used by foreign parties in an attempt to hinder the protection of Traditional Cultural Expressions (TCEs) in a country, because of the potential economic benefits resulting from their use, this condition is clearly very vulnerable to misappropriation committed by foreign parties, destruction of cultural values, and exploitation. This study also aims to find out how countries, especially Indonesia, provide protection for Traditional Cultural Expressions. Because of the importance of protecting Traditional Cultural Expressions, doctrinal and comparative research is directed at finding problem solvers. After conducting research, the public domain should not be placed on Traditional Cultural Expressions because it would violate the secret character of many intangible, sacred, and secret elements that living things have to cultural heritage and would highlight the deterioration and unauthorized appropriation of cultural values. And some countries have regulated the protection of Traditional Cultural Expressions in different ways through IPR regimes or sui generis. However, there is a need for a model law in the form of collective agreements between countries to protect Traditional Cultural Expressions owned by indigenous peoples or owning communities.